2021
DOI: 10.1021/acs.cgd.1c00185
|View full text |Cite
|
Sign up to set email alerts
|

Anion–Cation Bonding and Structure–Property Relationships of Three cyclo-Pentazolate Compounds

Abstract: The all-nitrogen cyclo-pentazolate (c-N5 –) anion has attracted considerable attention because of its potential applications in high-energy density materials. However, achieving comprehensive insight into the chemical properties of c-N5 – is challenging because of its complex chemical behavior. To elucidate this behavior, we stabilized the c-N5 – anion by forming its triaminoguanidinium (1) and 4-nitro-(3,4-diamino-1,2,4-triazolium-5-yl)-1H-pyrazolium (2) salts and its cocrystal (3) of a 1:1 ratio of 3,3-dinit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…[4] The stability of cyclo-N 5 À anions is influenced by different coordination modes, and recent research has confirmed that π-π interactions and hydrogen bonding are crucial for stabilizing cyclo-N 5 À anions. [5] The cyclo-N 5…”
Section: Introductionmentioning
confidence: 99%
“…[4] The stability of cyclo-N 5 À anions is influenced by different coordination modes, and recent research has confirmed that π-π interactions and hydrogen bonding are crucial for stabilizing cyclo-N 5 À anions. [5] The cyclo-N 5…”
Section: Introductionmentioning
confidence: 99%
“…5a-f) represent areas of high and low close contacts, respectively. 31,32 Of the six crystal environments of cyclo-N 5 − anions in compound 1 (named 1i- 1vi), 1i, 1ii, 1iv, and 1v are stabilized by five hydrogen bonds with water molecules, and 1iii and 1vi are stabilized by four hydrogen bonds with water molecules. The Hirshfeld surfaces of 1i, 1ii, 1iv, and 1v are pentagonal, with areas of high close contact mainly distributed at the edges of the surfaces, while those of 1iii and 1vi have an irregular block shape, with an uneven distribution of areas of high close contact.…”
Section: Hirshfeld Surface Analysis and Noncovalent Interactionsmentioning
confidence: 99%
“…From the published physicochemical properties, the cyclopentazolate salts (CPSs) have exhibited substantial difference from the conventional HEDMs, e.g. trinitrotoluene (TNT), Royal Demolition Explosive (RDX) and High Melting Explosive (HMX), in terms of the decomposition temperature and density, together with the formation heat and the detonation velocity [11,12]. To understand these differences, computational work is quickly followed, employing the DFT calculation [7,13] and ab initio calculations [14] based on the single-crystal structures of CPSs, which leads to a better understanding of the noncovalent interaction between molecules and the energy change after bond-breaking [15].…”
Section: Introductionmentioning
confidence: 99%